Answer:
x = -9, -3
Step-by-step explanation:
x^2 + 12x + 27 = 0
We need 2 numbers whose product is + 27 and whose sum is + 12. These are 3 and 9. So the factors are:-
(x + 3)(x + 9) and this = 0
So (x + 3) = 0 or x + 9 = 0
x = -3 , -9
=-30
-2*-3=6
-1*5=-5
6 x -5=-30
Answer:
sqrt(x)
Step-by-step explanation:
1/ ( x^(-3/6))
We can simplify the fraction
1/ ( x^(-1/2))
A negative exponent means that since it is in the denominator, it goes to the numerator. It still keeps the exponent.
x^ (1/2)
sqrt(x)
The value of the given expression is ![\frac{-13}{20}.](https://tex.z-dn.net/?f=%5Cfrac%7B-13%7D%7B20%7D.)
Solution:
Given expression is
.
Let us first convert mixed fraction into improper fraction.
![3\frac{2}{5}=\frac{(3\times5)+2}{5}=\frac{17}{5}](https://tex.z-dn.net/?f=3%5Cfrac%7B2%7D%7B5%7D%3D%5Cfrac%7B%283%5Ctimes5%29%2B2%7D%7B5%7D%3D%5Cfrac%7B17%7D%7B5%7D)
Substitute this in the given expression.
![\frac{3}{4} \times3\frac{2}{5}-\frac{5}{5}=\frac{3}{4} \times\frac{7}{15}-\frac{5}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B4%7D%20%5Ctimes3%5Cfrac%7B2%7D%7B5%7D-%5Cfrac%7B5%7D%7B5%7D%3D%5Cfrac%7B3%7D%7B4%7D%20%5Ctimes%5Cfrac%7B7%7D%7B15%7D-%5Cfrac%7B5%7D%7B5%7D)
![=\frac{21}{60}-\frac{5}{5}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B21%7D%7B60%7D-%5Cfrac%7B5%7D%7B5%7D)
To simplify the above expression, 21 and 60 are cancelled by 3.
![=\frac{7}{20}-\frac{1}{1}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B7%7D%7B20%7D-%5Cfrac%7B1%7D%7B1%7D)
Do cross multiplication to make the denominator same.
![=\frac{7}{20}-\frac{20}{20}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B7%7D%7B20%7D-%5Cfrac%7B20%7D%7B20%7D)
![=\frac{7-20}{20}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B7-20%7D%7B20%7D)
![=\frac{-13}{20}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-13%7D%7B20%7D)
The value of the given expression is ![\frac{-13}{20}.](https://tex.z-dn.net/?f=%5Cfrac%7B-13%7D%7B20%7D.)